Phenylethanoids from the Root of Rosa rugosa and their Biological Activities - Li, Yinke; Ma, Jingjing; Yang, Liying; Shu, Lidang; Shen, Yanqiong; Hu, Qiufen; Xia, Zhangyuan (Asian Journal of Chemistry, 2013)
A new phenylethanoids, rugethanoid C (1), together with five known phenylethanoids (2-6), were isolated from the roots of Rosa rugosa. Their structures were determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. rugethanoid C (1) was tested for their anti HIV-1 activities and cytotoxicities. The results showed that rugethanoid C (1) has moderate potential cytotoxic ability and anti HIV-1 bioactivities.